Forest Structure and Composition Diverge Following Harvesting Compared to a Spruce Budworm Choristoneura fumiferana (Clem.) Outbreak - Kneeshaw, Daniel D.; De Grandpré, Louis; D’Orangeville, Loïc; Marchand, Maryse; Moisan-Perrier, Jeanne; Robert, Louis-Etienne; Bouchard, Mathieu (Frontiers in Forests and Global Change, 2022)
Balsam fir (Abies balsamea) is the most vulnerable species to the spruce budworm (SBW), one of the most devastating defoliators in the world. For decades, pest managers have advocated for reducing its abundance in the landscape to minimise losses to the spruce budworm (Choristoneura fumiferana). Although reduction of fir occurred during the endemic phase of the SBW cycle, there is little information about the extent to which this general principle (reduction of fir) was applied during an outbreak and whether it occurs at both stand and landscape levels. The objective of this paper is to compare the effect of insect and harvest disturbances on forest structure during the 1970-80s outbreak in Québec. We evaluate whether, i) forest management activities targeted fir forests and whether patch size of host species influences management or SBW disturbance, ii) SBW outbreaks and logging have similar or divergent effects on forest composition. Although data are from an earlier outbreak, they are at a scale rarely studied and will be useful in guiding decisions made at larger scales in the current and future outbreaks. Our results show that spruce was targeted preferentially by harvesting (up to 69% of plots) during the outbreak period, while it represented less than one third of plots defoliated by the spruce budworm. On the other hand, fir stands represented up to 75% of plots that were defoliated by the SBW but <35% of plots that underwent harvesting. Harvesting targeted large blocks of spruce forest more than large blocks of fir-dominated forest while the opposite was observed for the SBW. In terms of regeneration, SBW tends to reduce fir and favour spruce recruitment, along with non-host species, whereas the opposite tendency was observed following harvesting. In terms of spatial organization of stands , our results support the suggestion that small stands of fir and large stands of spruce undergo the least spruce budworm damage. Thus, in order to attenuate SBW impacts in the future, efforts should be made to ensure that spruce recruitment is favoured and that its abundance increases at both the stand and landscape scale